Design and implementation of an intelligent system forurban vertical agriculture inthe framework of the Internetof Things (IoT) - Fagua Fagua, Andrea Liliana; Najar Pacheco, Jose Custodio; Rojas Moreno, Wilmar Yovany (Ingeniería Solidaria, 2025)
Introduction: This article is the product of research conducted on the Internet of Things and its application to urban agriculture, carried out at the Fundación Universitaria Juan de Castellanos in the year 2022. The goal is to create ideal conditions by controlling irrigation, temperature, and humidity. Investigate the needs of the plants and seek to maximize production with vertical models, in addition to implementing an IoT interface to monitor the crop. Problem: Growing in limited urban spaces is difficult due to lack of time and supervision. Importance: Impact on the availability of healthy foods. Objective: Design an IoT system for urban gardens, efficient in resources, with online monitoring and analysis of environmental variables to improve cultivation in small spaces. Methodology: The methodology involves investigating the needs of the plants and designing vertical cultivation models. IoT is used to capture data and the system is evaluated by analyzing environmental variables. Results: The results demonstrate that the IoT system is effective in the monitoring, control, and efficient use of water, promoting healthy growth of vegetables with remote supervision. Conclusion: Urban vertical farming with IoT is an innovative solution to grow vegetables in limited spaces, improving resource efficiency and promoting technological agriculture. Originality: It lies in the combination of urban agriculture with IoT technology, which allows for the precise monitoring and control of growing conditions in real time. Limitations: Adapt the system to fast-growing seedlings and deliver prototypes with germinating seedlings, reliance on Internet connectivity, with limitations in some areas.